Designing three dimensional graphic objects using the polynomial of trigonometric curves with a shape parameter and the sweep surface head of project / Noor Khairiah Razali and Nursyazni Mohamad Sukri - Razali, Noor Khairiah; Mohamad Sukri, Nursyazni (Research Management Institute (RMI), 2012)
The desired shape of Bezier and B-spline curves can be meeting by adjusting the control points, knot vectors and degrees. This adjustment was complicated and costly. In this project, the trigonometric polynomial with a shape parameter curves and rotational sweeping method was introduced as an alternative method in generating the variety of symmetrical three dimensional objects and designs easily, flexibly and less costly in time of working the calculation. The trigonometric polynomial curves were analogous to B-spline curves, but the curves can be manipulated based on the value of shape parameter, on a fixed control polygon and same control point. This property was an advantage in generating three dimensional objects using rotation sweep surface method, where the curve was rotated at y-axis with 360o degree. This polynomial was studied based on open and close uniform curves and applied in rotational sweep method to create three dimensional objects. The shape of the vase was generated as examples of three dimensional objects and the variety designs were produced by manipulated the value of shape parameter.